Immunological Response of Interleukin-6 on Cantang Hybrid Grouper (Ephinephelus sp.) By Induction Of Protein Brachionus sp. - Kumalaningrum, Dwi Retna; Yanuhar, Uun; Musa, Mohammad; Martiningsih, Nur Fauzi-yah (Department of Aquaculture, 2024)
This study examines the role of Brachionus sp protein on the interleukin-6 pro-inflammatory immune system in Cantang grouper infected with Viral Nervous Necrosis (VNN). The purpose of this study was to determine the protein content of Brachionus sp. which has the potential as an antivirus and to find out the benefits of Brachionus sp. on the expression of Interleukin-6 as an indicator of increased fish body defense system against VNN. Testing of Brachionus protein by injection at doses of 35 µl, 105 µl, and 170 µl /150 gram Cantang grouper. The results showed that the lowest decrease was at a dose of 105 µl/150-gram Cantang groupers. In addition, Brachionus sp. contains 3 protein bands with molecular weights of 122.73 kDa, 75.49 kDa, and 13.77 kDa.